2023
DOI: 10.3390/jzbg4010006
|View full text |Cite
|
Sign up to set email alerts
|

The Societal Value of the Modern Zoo: A Commentary on How Zoos Can Positively Impact on Human Populations Locally and Globally

Abstract: Modern zoos and aquariums have evolved greatly since the end of the Second World War, to become centres of conservation excellence and scientific institutions for the study of animal behaviour, ecology, husbandry management. Whilst the impact of zoos and aquariums to biodiversity conservation, population management and advancement of species care is well documented, their positive impacts on society (including the communities that they are located within) is less well known. The four established aims of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…An integral aim of the modern zoo is education ( Kleiman, 1985 ), which adds value to the zoo’s living collection, its operations and impacts on society more widely ( Greenwell et al, 2023 ). Zoos have well planned and structured educational offerings for pre-school, school, college, and university-level groups, and provide a wealth of informal educational materials and activities for general visitors too.…”
Section: Keep Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…An integral aim of the modern zoo is education ( Kleiman, 1985 ), which adds value to the zoo’s living collection, its operations and impacts on society more widely ( Greenwell et al, 2023 ). Zoos have well planned and structured educational offerings for pre-school, school, college, and university-level groups, and provide a wealth of informal educational materials and activities for general visitors too.…”
Section: Keep Learningmentioning
confidence: 99%
“…A smaller proportion of this overall estimate will be part of accreditation (e.g., European Association of Zoos & Aquaria, EAZA; Association of Zoos & Aquariums, AZA) or membership (British & Irish Association of Zoos & Aquariums) organizations that uphold education, conservation and research initiatives and promote good animal welfare ( Marcy, 2021 ; BIAZA, 2023a ; EAZA, 2023a ). Modern zoos are consistently aiming to promote both animal welfare and positive human wellbeing in terms of their outputs and operations ( Rose and Riley, 2022 ) and therefore have value to the human populations that work at them, live around them, visit them and engage with their work on a local or global level ( Greenwell et al, 2023 ). This value can be extended if zoo visits can enhance mental health, encourage a deeper understanding of nature, and foster a greater appreciation of the natural world.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their important roles as sites of conservation, zoos are of value to the visitors who attend them for education and recreation, as evidenced by their strong global patronage [ 1 , 2 ]. Zoos are not without their challenges, however, particularly in relation to public perceptions of the ethics of captivity for charismatic and socially complex animals such as elephants ( Loxodonta africana and Elephas maximus ).…”
Section: Introductionmentioning
confidence: 99%
“…As zoos strive to provide excellent welfare for their individual residents while addressing the concerns of their visitors, it is essential to delve beyond the caregivers’ and elephants’ experiences of their interactions and consider how patrons perceive those interactions. Visitor satisfaction is paramount for zoos, as it directly impacts their economic viability, which then affects zoos’ capacity to fund conservation efforts, provide stimulating environments for their resident animals, and employ skilled staff, among other community contributions [ 2 ]. Furthermore, this research explores both consumer satisfaction (visitors’ likes/dislikes) with an organizational product (e.g., tours that require a separate purchase from front-gate admission) and animal satisfaction (expressed through visitors’ perceptions of elephants’ emotions and welfare states that are then viewed through the lens of an established welfare assessment tool).…”
Section: Introductionmentioning
confidence: 99%
“…Education, conservation, research, and recreation are important operation objectives found in many zoos’ mission statements [ 3 , 4 , 5 , 6 , 21 , 22 ]. Animal welfare supports each of those target activities, and should therefore be a key mission objective for all zoological facilities.…”
Section: Introductionmentioning
confidence: 99%